### Basic Concept for problems on ages :

**1.** If the present age of ‘A’ is ‘x’ years, then

‘n’ years ago => Age of ‘A’ was (x-n) years.

‘n’ years after => Age of ‘A’ will be (x+n) years.

**2.** In general, at the starting of the solution we have to assume the present age of one person. It is better to assume the present age = ‘x’ years.

**3.** So I advise you to assume the age of the younger person = ‘x’ years.

**4.** If the present age ‘A’ and ‘B’ are ‘x’ and ‘y’ years respectively, then

‘n’ years ago => Age of ‘A’ and ‘B’ were (x-n) and (y-n) years respectively.

‘n’ years after => Age of ‘A’ and ‘B’ will be (x+n) and (y+n) years respectively.

**5.** The age difference between you and your friend is let’s suppose 6 years. And after 10 or 15 years this will be same, because clock will run equally for both of you.